Study on microcosmic properties and temperature simulation of foamed polypropylene composites - Dongsheng Yang; Xin Yang; Qi Chen; Wei Gong; Jincheng Zhong (Scientific Reports)
Abstract The injection molding procedure and the compression molding procedure of foamed polypropylene composite are studied. The pore diameter, pore density, and microscopic topography for polypropylene composites was studied by experiments of slicing samples. The foamed temperature is very important for foamed property of the foamed polypropylene composite materials. To analyze the effect of temperature distribution, the virtual boundary meshfree Galerkin method (VBMGM) was employed the radial basis function interpolation method to obtain a detailed discretization formula. The temperature of experiment and numerical calculation from zone a to zone d in different zones of the injection molding procedure is reduced from 406.35 K to 311.63 K; the temperature from Ma zone to Md zone in the compression molding procedure is reduced from 326.35 K to 309.14 K. The experimental observation of the injection molding procedure shows that the foamed property in zone c is ideal, and the average pore diameter and pore density are 26.5 µm and 2.43×109 cells·cm−3 respectively. According to the experimental observation of compression molding process, the foamed property in Md zone is ideal, and the average pore diameter and pore density are 131.2 µm and 6.3×104 cells·cm−3. These results are of great significance to the foam molding of polypropylene composites.